COFFEE PROGENY AVALIATION OBTAINED FROM CROSSING AMONG CATUAÍ AND HYBRID OF TIMOR - CARVALHO, Alex Mendonça de; PEREIRA, Antonio Alves; CARVALHO, Gladyston Rodrigues de; MENDES, Antonio Nazareno Guimarães; BOTELHO, Cesar Elias (Scientia Agraria, 2008)
The resistance to the rust is the research which has received more attention in the coffee breeding programs since the entrance in Brazil, in 70´s decade, when the damages started to cause illness in the coffee cropping. However, to obtain one cultivar it’s necessary to have a good plant adaptability and phenotypic stability in several places. The progeny evaluations in several places are an important stage in the final phase of a breeding program. This work aimed to evaluate the behavior of coffee plants progenies in two places, originated from ‘Catuai’ and ‘Hybrid of Timor’ coffee variety crossing according characteristics of the production, vegetative aspects and the grains sieve. The experiments were installed in December of 1999 at Federal University of Lavras campus and at particular farm in Campos Altos City. The experimental design adopted was randomized block, with three replications and six plants per plot spaced 3.5 by 1.0 m inter row and rows, respectively. Twenty five progenies were evaluated, considering as period: 2003/2004, 2004/2005, 2005/2006 and 2006/2007 harvest years. It was evaluated the yield, vigor and grains classification by sieve. Coffee plant progenies varied in vigor, production and classification for sieve type in the two locations evaluated and the progenies H 337-13-1, H 419-8-13-3 and H 514-7-16-3 presented good behavior in the locations, evidencing high adaptability and production stability.